Teacher Accompaniment in Improving Digital Literacy Through Metamorphosis Props Training QR-Code - Widiyati, Evita; Kibtiyah, Asriana; Bahrodin, Ariga (LPPM Universitas Yudharta Pasuruan, 2024)
The purpose of this activity is to provide insight and increase teacher knowledge at MI Al-Ittihad about making Algameta media, how to make QR-Code online, and the implementation of teaching aids with digital literacy. The service team uses the Participatory Action Research method in providing participatory training which makes educators as objects to be able to use digital media in the form of QR-Code. The service team participatively provides training at MI Al-Ittihad and involves educators to encourage changes in the teaching and learning process towards a creative, innovative and fun direction. Based on the results of the pretest and posttest that have been carried out, it can be seen that the service is running successfully. The results achieved from this activity are in the form of increased teacher creativity in innovating learning on teaching aids implemented with digital media, increasing teacher ability to make Algameta assisted by QR-Code digital media and increasing teacher digital literacy. This is evidenced by the Paired Sample Test which is known that the Sig. (2-tailed) of 0.021 <0.05, it can be concluded that by holding this training can improve the competence of the training participants.